2020
DOI: 10.3389/fonc.2020.573501
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Serum Exosomal MicroRNA Nomogram for the Preoperative Prediction of Lymph Node Metastasis in Esophageal Squamous Cell Carcinoma

Abstract: Preoperative prediction of lymph node (LN) metastasis is accepted as a crucial independent risk factor for treatment decision-making for esophageal squamous cell carcinoma (ESCC) patients. Our study aimed to establish a non-invasive nomogram to identify LN metastasis preoperatively in ESCC patients. Construction of the nomogram involved three sequential phases with independent patient cohorts. In the discovery phase ( N = 20), LN metastasis-associated microRNAs (miRNAs) were selected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Recently, emerging evidence demonstrated that exosomal miRNAs modulate the tumor lymph node metastasis, which is favorable for tumor growth and invasion, by remodeling extracellular matrix, promoting tumor angiogenesis, inducting in ammation and immune suppression [26][27][28]. Previous studies indicated that serum exosomal miR-766-3p level was association with lymph node metastasis, which cloud predict ESCC lymph node metastasis (AUC = 0.778; 95% CI, 0.672-0.884) [22]. Another study pointed that four exosomal miRNAs model identi ed lymph node metastasis metastases with an AUC value of 0.865 [23].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, emerging evidence demonstrated that exosomal miRNAs modulate the tumor lymph node metastasis, which is favorable for tumor growth and invasion, by remodeling extracellular matrix, promoting tumor angiogenesis, inducting in ammation and immune suppression [26][27][28]. Previous studies indicated that serum exosomal miR-766-3p level was association with lymph node metastasis, which cloud predict ESCC lymph node metastasis (AUC = 0.778; 95% CI, 0.672-0.884) [22]. Another study pointed that four exosomal miRNAs model identi ed lymph node metastasis metastases with an AUC value of 0.865 [23].…”
Section: Discussionmentioning
confidence: 99%
“…No patients had any anti-cancer treatment before surgery. The ESCC with lymph node metastasis was de ned according the previous study [22]. Based on histopathology, 79 ESCC were divided into two groups: 42 ESCC with lymph node metastasis and 37 ESCC without lymph node metastasis .…”
Section: Patients and Samplesmentioning
confidence: 99%
See 3 more Smart Citations